PERAN AKREDITASI DAN STANDAR MUTU DALAM MENINGKATKAN KINERJA LEMBAGA PENDIDIKAN - Firanita Putri; Siminto; Musyarapah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Aaccreditation and quality standards are the two main pillars in efforts to improve the performance of educational institutions in Indonesia. This article aims to comprehensively examine how the accreditation process carried out by the National Accreditation Board (BAN) and the implementation of quality standards based on the National Education Standards (SNP) contribute to improving the quality and performance of educational institutions, especially madrassas and Islamic schools. The method used is a systematic literature study by examining various academic sources from national and international journals and books. The results of the study show that accreditation does not only function as an external evaluation instrument, but as a catalyst for institutional transformation that encourages a culture of quality in a sustainable manner. Quality standards that are consistently applied have been proven to improve the competence of educators, the effectiveness of school management, and stakeholder satisfaction. The conclusion of this article emphasizes that the synergy between accreditation and the internalization of quality standards based on Islamic values such as itqan (work perfection) and amanah (responsibility) will produce superior, accountable, and highly competitive educational institutions. Keywords: accreditation, quality standards, educational institutions